2004
DOI: 10.1111/j.1746-1561.2004.tb06627.x
|View full text |Cite
|
Sign up to set email alerts
|

School‐Based Health Centers and Academic Performance: Research, Challenges, and Recommendations

Abstract: School-based health centers (SBHCs) provide physical and mental health services on school campuses to improve student health status, and thereby potentially facilitate student academic success. With a growing emphasis on school accountability and the simultaneous dwindling of resources at the federal, state, and local levels, SBHCs face increasing pressures from school administrators and funders to document their impact on student academic achievement. This article reviews the methods, findings, and limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 10 publications
4
74
0
1
Order By: Relevance
“…Alternative school students who used the services of an SBHC were twice as likely to stay in school and graduate as students who did not use the center (McCord et al, 1993). Geierstanger and Amaral (2005) cautioned that although there is evidence that SBHCs have a positive impact on academic variables for students, many of the studies that document the connection between SBHCs and academic outcomes are based on small sample sizes. Further research is necessary to better understand the contribution of SBHCs to academic success.…”
Section: School-related Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…Alternative school students who used the services of an SBHC were twice as likely to stay in school and graduate as students who did not use the center (McCord et al, 1993). Geierstanger and Amaral (2005) cautioned that although there is evidence that SBHCs have a positive impact on academic variables for students, many of the studies that document the connection between SBHCs and academic outcomes are based on small sample sizes. Further research is necessary to better understand the contribution of SBHCs to academic success.…”
Section: School-related Outcomesmentioning
confidence: 98%
“…SBHCs have long been recognized as having a positive effect on these salient factors of enhanced academic outcomes (Shaw, Kelly, Joost, & Parker-Fisher, 1995). The following summary of academic outcome indicators is derived in part from the excellent review article by Geierstanger, Amaral, Mansour, and Walters (2004), supplemented by additional studies reported in the literature on SBHCs.…”
Section: School-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weismuller et al [9] described the effect of school nurse interventions on decreasing the rate of student absenteeism because of their increased interaction with students who are absent from school and by giving health guidance to the students. In similar vein [16] found that there is a strong correlation between student attendance (including absenteeism and tardiness) and SBHCs. Students are more likely to attend school if there is an SBHC available, because this provides a margin of health safety and security for the students.…”
Section: Presence Of School Nursesmentioning
confidence: 60%
“…Students are more likely to attend school if there is an SBHC available, because this provides a margin of health safety and security for the students. It provides them with resources to utilize when they have health concerns, especially on days that they become ill [16].…”
Section: Presence Of School Nursesmentioning
confidence: 99%